Structure and thermal stability of cellulose nanocrystal/polysulfone nanocomposites. (March 2020) - Onbattuvelli, Valmikanathan P.; Enneti, Ravi K.; Simonsen, John; Kate, Kunal H.; Balla, Vamsi K.; Atre, Sundar V.
Graphical abstract: Highlights: Thermal stability of cellulose nanocrystal (CNC)/polysulfone nanocomposites was studied. Effect of heating rate and CNC content was evaluated. Master decomposition curves were developed to estimate thermal stability. Stabilizing effect of PSf matrix suppressed CNC filler thermal degradation. Thermal degradation of nanocomposites followed 1 st or 2 nd order reaction kinetics. Abstract: The thermal stability of nanocomposites of cellulose nanocrystals (CNC) dispersed in polysulfone (PSf) was studied to understand the influence of heating rate and CNC concentration using thermogravimetric analysis (TGA). While heating rate was found to have a positive influence on the degradation onset temperature and the maximum degradation rate ( T max ) of these nanocomposites. The influence of CNC concentration appeared to be relatively low on these parameters. PSf/CNC nanocomposites with up to 2 wt.% CNC were found to follow first order degradation kinetics and at higher concentrations, better fit was seen with second-order degradation kinetics. The activation energy associated with nanocomposites degradation, determined using Kissinger method, revealed strong stabilizing effect of PSf matrix on CNC filler. FTIR analysis showed signature peak shifts that correlated with PSf/CNC interactions. On the other hand, the CNC filler had marginal influence on the stability of PSf matrix. Master decomposition curve (MDC) and weight-time-temperature plots were constructed from the obtained activation energies to describe the time-temperature dependence of the PSf/CNC nanocomposite pyrolysis.